Policy Analysis of Local Government Strategies for Stunting Reduction in South Bolaang Mongondow Regency - Zulkarnain Kamaru; Marwan Djafar; Apriyanto Nusa (Cattleya Darmaya Fortuna, 2025)
Stunting remains a major public health and development challenge in Indonesia, requiring integrated and sustainable policy interventions at both national and local levels. This study analyzes the implementation of local government policies in addressing stunting in South Bolaang Mongondow Regency, with a particular focus on identifying factors that hinder effective policy execution. The research is grounded in an empirical legal approach combined with a sociological juridical perspective, examining how normative legal frameworks are applied in social reality. Data were collected through field observations, in-depth interviews with key stakeholders involved in the Stunting Reduction Acceleration Team at the regency, sub-district, and village levels, as well as documentation studies of relevant regulations and policy instruments. The findings reveal that although the local government has established regulatory and institutional frameworks aligned with national stunting reduction policies, policy implementation has not been fully optimal. Several inhibiting factors were identified, including limited policy communication and understanding at the village level, inadequate human and financial resources, varying levels of commitment among policy implementers, weak inter-sectoral coordination, socio-cultural perceptions within the community, and deficiencies in data management and utilization. These constraints contribute to fragmented interventions and reduce the effectiveness of policy convergence efforts. The study concludes that the success of stunting reduction policies at the local level is not solely determined by regulatory completeness, but also by governance quality, institutional capacity, and community participation. This research contributes to the development of empirical legal studies by providing an integrated analysis of policy implementation challenges and offers insights for strengthening local governance in accelerating stunting reduction.